2007
DOI: 10.2175/193864707787223574
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Two-Phase Anaerobic Digestion System

Abstract: The Metro Wastewater Reclamation District (Metro District) provides wholesale wastewater transmission and treatment service to 55 local governments in the Denver metropolitan area. Solids processing at the Central Treatment Plant (CTP) consists of dissolved air flotation (DAF) thickening of waste activated sludge (WAS), anaerobic digestion of blended primary sludge and thickened WAS, dewatering with high-solids centrifuges, land application at the Metro District's METROGRO Farm located approximately 100 miles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Barnes et al (2007) reported on the findings and response of the system to variations in the volatile solids loading and ferric chloride addition to digester feed, as well as the important factors that need to be taken into account in designing and implementing acid phase digestion versus gas phase digestion, and phased digestion overall. A reduction in solids loadings to the acid phase digester was the result of a program of water conservation in a Denver sewershed, resulting in a reduction in the volatile solids loading rate to the acid phase digester to less than the design rate The VSR response was less than expected as a result, but .…”
Section: Figure 2 Impact Of Advanced Digestion Mode To Biosolids Promentioning
confidence: 99%
“…Barnes et al (2007) reported on the findings and response of the system to variations in the volatile solids loading and ferric chloride addition to digester feed, as well as the important factors that need to be taken into account in designing and implementing acid phase digestion versus gas phase digestion, and phased digestion overall. A reduction in solids loadings to the acid phase digester was the result of a program of water conservation in a Denver sewershed, resulting in a reduction in the volatile solids loading rate to the acid phase digester to less than the design rate The VSR response was less than expected as a result, but .…”
Section: Figure 2 Impact Of Advanced Digestion Mode To Biosolids Promentioning
confidence: 99%